To investigate the mechanical/adhesion properties and mechanical reliability of thin films in electronics materials - Wan, Kai Tak (2008)
Thin-layered structures of dissimilar materials have found increasing applications in many new advanced technologies. For instance, thin-layered structure is an essential feature in electronics packaging and microelectromechanical system (MEMS) device. In these devices, delamination due to crack propagation of the interface between dissimilar materials is a common failure mode and is strongly dependent on the adhesion strength of the interface.